The Efficacy of Thai Traditional Medicine on Fracture Treatment : Amphoe Pichai, Changwat Uttaradit - Amponnavarat, Todsanat (Journal of Health Science of Thailand, 2018)
From the year 2005 to 2007 accident injuries cases had increased from 681 to 771 and 839 cases in Phichai hospital, Changwat Uttaradit. Some patients with fractured bone, having faith in traditional practitioners, opted for traditional healing.The Phichai hospital, therefore, conducted a descriptive research on the efficacy of traditional medicine on fracture treatment. The objectives of the research were to study a traditional practitioner background in Amphoe Phichai, Changwat Uttaradit, treatment process, concept of traditional treatment on fracture and case histories of patients. The research included 30 cases of fracture patients who visited the practitioner. The treatment outcomes evaluated by an orthopedist indicated that: 36.67 percent completely healed, including 7 / 13 clavicle fracture cases. However only 2 cases in each group with broken arms,and with legs were proclaimed completely cured. In conclusion, the Thai traditional practitioner can treat calvicle fracture patients effectively. But there were low percentage of complete healing for arm and leg fracture patients. It is then recommended that the practitioner should change some of their practices to reduce disabilities possibly caused by traditional treatment.